The Understanding Of Religious Moderation In Social Life Context - Sinollah, Sinollah; Muar, Muhammad Romli (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Indonesia is a pluralistic country with various races, ethnicities, and religions. Tolerance is one of the national glues within the framework of Bhinneka Tunggal Ika. Purwodadi Village is a village with unique religious moderation; there is only when 1 joint cemetery from various existing religions, and it does not recognize race, ethnicity, and religion. The results of interviews and observations show that the residents of Purwodadi Village are accustomed to carrying out social activities together so as to create a continous sense of security and the absence of social inequality. of course, this condition can be used as a role model for religious moderation in Indonesia for terms of social life.